A Case of Tubercular Intramedullary Abscess in An Infant - Singh, Anish M; Shrestha, Prabin; Sah, Hemant; Shrestha, Reshma (Nepal Journal of Neuroscience, 2016)
Spinal abscess in pediatric age group is a rare entity. Tubercular type is even rarer and it has been found to be associated with patent dermal sinus. Very few cases have been reported so far. We present a 2-month-old baby with gradually progressing paraparesis. There was a small dermal sinus in the lower area of right buttock which was discharging pus. MRI was done which showed intramedullary fluid collection at the level of lower lumbar and sacral spine suggesting abscess formation. Patient party was suggested for surgical exploration and histopathological evaluation. However, they denied and thus baby was put on steroid therapy. The baby gradually improved. However he started having paraparesis again and even worse than before. Repeat MRI showed intramedullary collection more than the previous MRI. Again surgical option was given and finally surgery done. Right hemilaminectomy was done from L3-4-5-S1and dura exposed. Dura was incised and spinal cord, conus and cauda equina exposed which were swollen and congested. Midline myelotomy was done opening the intramedullary. Free flow of thick pus was observed. Dermal sinus was excised and closed. Pus and small pieces of granulation tissue was sent for culture and cytological examination which showed features of tuberculosis. Antitubercular treatment was started and the baby became much better. Nepal Journal of Neuroscience 12:43-45, 2015